The "Demonic Other” and the Colonial Figures in Kipling’s The White Man’s Burden and Taher’s Sunset Oasis: A Comparative Study - Shehata, Abdel Kareem (International Journal of Language and Literary Studies, 2022)
In 1899, The British poet Rudyard Kipling directed his poem, The White Man’s Burden, to the United States on the occasion of the invasion of the Philippine Islands. In his poem, Kipling mainly encourages the States to occupy the Islands. Kipling also draws a portrait of the colonized peoples. In 2007, the Egyptian novelist Bahaa Taher published his novel (Waht Al Ghoroub), Sunset Oasis. In his novel, Taher presents a group of Egyptian, English, Irish and Circassian characters who live in Egypt during and after the Urabi Revolution (1882). The first aim of this paper is to show the main features of the picture of the colonized people in Kipling’s poem. The second aim is to highlight the traits of the pictures of the characters, who are terribly influenced by the imperial project throughout the history in Taher’s novel. Comparing Kipling’s and Taher’s pictures is another important aim of the paper. The paper will achieve these aims in the light of the postcolonial theory and the paper comes in two parts and a conclusion.